Parameter Estimation of the Mixed Negative Binomial and Two-Parameter Lindley Distribution: Maximum Likelihood Method - เด่นเทศ, สุนทรี; ทองธีรภาพ, อำไพ; โพธิ์สุวรรณ์, วินัย (Princess of Naradhiwas University Journal, 2018)
Recently, the negative binomial two-parameter Lindley distribution. In this article, the parameter estimation of the negative binomial two-parameter Lindley distribution using the maximum likelihood estimation method will be developed. A Monte Carlo simulation is applied in order to compare the efficiency of model parameter estimation using the the maximum likelihood estimation method based on mean square error of estimates. The finding results of simulation study was show that the the maximum likelihood estimates seem to have high-efficiency when the sample size becomes large. In addition, the negative binomial two-parameter Lindley distribution is applied to real data sets, we found that it can be fitted to the selected data sets. Each data set is fitted with the negative binomial two-parameter Lindley distribution, Poisson, negative binomial, and negative binomial Lindley distribution using the maximum likelihood estimation method. By comparing these results based on the p-value of Anderson-Darling goodness of fit test for fit test, it shows that the negative binomial two-parameter Lindley distribution provided the best fit whencomparing to the other distributions